Risk Analysis and Estimation of Schedule Using Monte Carlo Simulation (International Journal of Engineering and Computer Science, 2018)
Unwanted schedule risk and improper estimates divert a project from achieving the goal of on-time successful delivery due to the presence of uncertainties. Most of the projects get delayed or cancelled due to this. So, using Monte Carlo Simulation technique a simulator is implemented in this paper which simulates the activity durations for analyzing schedule risk and providing reliable estimates of time.